2004
DOI: 10.1039/b402531h
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric synthesis and applications of β-amino Weinreb amides: asymmetric synthesis of (S)-coniine

Abstract: Conjugate addition of lithium (S)-N-benzyl-N-alpha-methylbenzylamide to a range of alpha, beta-unsaturated Weinreb amides proceeds with high levels of diastereoselectivity (>95% de). The beta-amino Weinreb amide products may be transformed into beta-amino ketones via reactions with Grignard reagents, while treatment with DIBAL-H furnishes beta-amino aldehydes. Trapping of the aldehyde via Wadsworth-Emmons reaction and subsequent manipulation offers an efficient route to homochiral delta-amino acid derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Thioketal 11 was converted into 2-phenylpiperidine hydrochloride 12 after hydrogenolysis realized in the presence of freshly prepared W2 Raney nickel 11 in refluxing ethanol, followed by a treatment with hydrochloric acid in diethyl ether. 12 Comparison of the specific rotation of 12 with those reported in the literature 13 showed that partial racemization occurs during the desulfurization step, probably due to a retro-Mannich-type reaction. In order to circumvent this problem, we decided to protect the nitrogen atom with a tert-butoxycarbonyl group to decrease its nucleophilicity (Scheme 4).…”
Section: Methodsmentioning
confidence: 92%
“…Thioketal 11 was converted into 2-phenylpiperidine hydrochloride 12 after hydrogenolysis realized in the presence of freshly prepared W2 Raney nickel 11 in refluxing ethanol, followed by a treatment with hydrochloric acid in diethyl ether. 12 Comparison of the specific rotation of 12 with those reported in the literature 13 showed that partial racemization occurs during the desulfurization step, probably due to a retro-Mannich-type reaction. In order to circumvent this problem, we decided to protect the nitrogen atom with a tert-butoxycarbonyl group to decrease its nucleophilicity (Scheme 4).…”
Section: Methodsmentioning
confidence: 92%
“…Elaboration of 6 into 7 with LiAlH 4 has already been reported. [41] Scheme 4. Synthesis of 2-phenylpiperidine (7).…”
Section: Entrymentioning
confidence: 99%
“…To test the practicability and synthetic utility of the protocol reported herein, the elaboration of compound 5a into the racemic (Ϯ)-2-phenylpiperidine (7) was explored and proved to be relatively straightforward (Scheme 4). The protocol to elaborate 5a into 6 [41] was achieved through desulfonation with sodium amalgam in methanol. Elaboration of 6 into 7 with LiAlH 4 has already been reported.…”
Section: Entrymentioning
confidence: 99%
“…In the past decades, many efforts have been devoted to construct carbon–nitrogen bond by employing different nitrogen nucleophiles and efficient catalyst . Because β ‐aminoketones and their derivatives are important synthetic intermediates for various pharmaceuticals and natural products, the development of efficient synthetic strategies to prepare β ‐aminoketones, has received great attention in modern organic and medicinal chemistry . Although a variety of methods have been reported, further atom‐economic routes to β ‐aminoketones still remain a hot topic in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%